2017
DOI: 10.1016/j.bmc.2016.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Studies of TAK1-centered polypharmacology with novel covalent TAK1 inhibitors

Abstract: Targeted polypharmacology provides an efficient method of treating diseases such as cancer with complex, multigenic causes provided that compounds with advantageous activity profiles can be discovered. Novel covalent TAK1 inhibitors were validated in cellular contexts for their ability to inhibit the TAK1 kinase and for their polypharmacology. Several inhibitors phenocopied reported TAK1 inhibitor 5Z-7-oxozaenol with comparable efficacy and complementary kinase selectivity profiles. Compound 5 exhibited the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…The cells were then separated and treated with 0.5 µM of one of the following: 5Z‐7‐oxozeaenol (OZ) (Sigma, St. Louis, MO), 5Z‐zeaenol (5Z) (CALBIOCHEM), or AZ‐TAK1 (3‐[(aminocarbonyl)amino]‐5‐[4‐(4‐morpholinylmethyl)phenyl]‐2‐thiophenecarboxamide) (Toronto Research Chemicals, Toronto, Canada), and incubated for 40–60 min. This concentration was selected based on successful TAK1 inhibition by OZ in various of cell types and models 30‐33 and no impact on cell viability was detectable. The groups were then stimulated with 10 or 100 ng/ml TNP‐BSA (Biosearch Technologies, Novato, CA) and/or 100 ng/ml SCF (Peprotech, Dollard des Ormeaux, QC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were then separated and treated with 0.5 µM of one of the following: 5Z‐7‐oxozeaenol (OZ) (Sigma, St. Louis, MO), 5Z‐zeaenol (5Z) (CALBIOCHEM), or AZ‐TAK1 (3‐[(aminocarbonyl)amino]‐5‐[4‐(4‐morpholinylmethyl)phenyl]‐2‐thiophenecarboxamide) (Toronto Research Chemicals, Toronto, Canada), and incubated for 40–60 min. This concentration was selected based on successful TAK1 inhibition by OZ in various of cell types and models 30‐33 and no impact on cell viability was detectable. The groups were then stimulated with 10 or 100 ng/ml TNP‐BSA (Biosearch Technologies, Novato, CA) and/or 100 ng/ml SCF (Peprotech, Dollard des Ormeaux, QC).…”
Section: Methodsmentioning
confidence: 99%
“…29 BMMC cultures were maintained at 37 • C and 5% CO 2 as previously described. 16 This concentration was selected based on successful TAK1 inhibition by OZ in various of cell types and models [30][31][32][33] and no impact on cell viability was detectable. The groups were then stimulated with 10 or 100 ng/ml TNP-BSA (Biosearch Technologies, Novato, CA) and/or 100 ng/ml SCF (Peprotech, Dollard des Ormeaux, QC).…”
Section: Mast Cell Culture Treatment and Activationmentioning
confidence: 99%
“…Previous studies showed that several compounds can decrease the expression of CD59 (van Breda et al, 2018) and inhibit XRCC5 (Tan et al, 2017). Therefore, further research on the mechanisms through which ellipticine targets XRCC5 and CD59 should be conducted.…”
Section: Bioinformatics Analysis Of Ellipticine In Inhibiting Breast mentioning
confidence: 99%
“…5ZO demonstrated increased efficacy compared to the Federal Drug Administration-approved Janus kinase inhibitor tofacitinib in RA cell models [ 35 ]. However, this molecule also potently inhibits a panel of at least 50 other kinases (RIOK3, MEK1,2,3,4,5 PDGFRB, FLT4, FLT1/3, KIT, TGFBR2) and forms a covalent bond with reactive cysteines in the activation loop of its targets, rendering it inadequate for therapeutic purposes owing to off target effects [ 60 , 69 ]. Despite the known limitations of 5ZO, it is still widely used to study TAK1 biology in contexts of disease.…”
Section: Tak1 As a Target For Inflammatory Disordersmentioning
confidence: 99%